ANALYSIS OF UNIVERSITY HELPDESK INFORMATION TECHNOLOGY GOVERNANCE USING COBIT 2019 AND FUZZY AHP - Syinsyina Arifa; Rizal Isnanto; Rinta Kridalukmana (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2023)
University Helpdesk as an information system service provider provided by PTIPD University assists students, staff, and lecturers in solving problems using information systems and networks, as well as updating information online and offline. Based on the Regulation Minister of Religion of the Republic of Indonesia Number 17 of 2013 to improve the quality of university delivery and services, and GUG (Good University Governance) implementation, governance framework is needed to align the vision, mission, and objectives. IT governance framework covering management, operational, maintenance, monitoring, and evaluation processes. The analysis of IT governance with COBIT 2019 resulted in the preparation of recommendations based on the mapping of the domain (area) of the 2019 COBIT design factors. These recommendations are needed for an analysis of the maturity level of PTIPD university helpdesk information technology governance. The research data were taken from annual reports and Key Performance Indicators, observations, and interviews. Based on Design Factors 1-11 to determine domain area, the result is needing improved governance perspective APO12-Managed Risk and DSS05-Managed Security Services. The focus area is risk management and service security management in terms of data and information. The expected ability level is at level 4, while the current ability level analysis is at level 2, the gap level analysis is 2 levels different. The result is to get 12 recommendations and 2 main recommendations using the Fuzzy-AHP method based on the weighting of the criteria of Regulation number 12 of 2012 the management of information technology in university.